Peningkatan Pengetahuan Ketahanan Ekonomi Melalui Keterampilan Otomotif Pada Siswa Ibnu Sina - Abdul Haris Subarjo (Institut Teknologi Dirgantara Adisutjipto, 2019)
Family resilience is crucial to achieving regional or regional resilience, then regional resilience will ultimately determine the achievement of national security. One part of family resilience is family economic resilience. To increase Family Economic Resilience can be by improving skills. Skills in the automotive field are one of the skills that have the potential to improve living standards. We can see this argument from the growth of motorized vehicles that are increasing from year to year which requires routine maintenance in order to operate optimally. This is an opportunity for people who are experts in the field of care. Aliyah Madrasah Ibnu Sina seeks to improve the skills of students in the automotive field, so that students can be independent and can improve the economic resilience of their families. The skills in the automotive field are also trying to be raised as the theme of community service activities involving Ibn Sina Madrasah Aliyah students. This activity is using training methods, lectures and brochures. As a result of this activity, students gain knowledge and insights that automotive skills can improve economic resilience.